Brain activity and autonomic regulation in untreated migraine patients - Monteiro, Isabel Oliveira; Novakovic, Juliana; Rodrigues, Miguel K.; Cunha Neto, Joel S.; Rela, Maíra O. V.; Oliveira, Mayron F. (Arquivos de Neuro-Psiquiatria, 2025)
Migraine causes intense pain, significant disability, deficits in attention and memory, slowed information processing, and cognitive disorders. However, it is unclear how migraine, cardiovascular, and cerebral issues impact daily life or relate to future adverse events.To evaluate the brain activity and autonomic regulation in untreated migraine patients.In the present case-control study, we compared untreated migraine patients with healthy controls. The participants underwent cognitive testing (Stroop Color Test, Trail Making Test, Addenbrooke's Cognitive Examination, and Reaction Time Test), brain activity measurement (MindWave Mobile), and autonomic regulation assessment via heart rate variability (Polar V800).No differences were found between the groups in terms of cognitive test scores. However, the healthy controls consistently showed increased variation in brain activity during the cognitive tests, while migraine patients exhibited decreased activity across all tests (p < 0.05). During the Stroop Color Test, the controls showed a positive change in brain activity (Δ = 5.12 ± 3.64) while the migraine patients showed a negative change (Δ = −5.41 ± 2.21). In addition, the control group demonstrated a normal autonomic response, with increased sympathetic activity (low-frequency [LF] band: 70.2–84.4 Hz) and decreased parasympathetic activity (high-frequency [HF] band: 29.6–15.6 Hz) during cognitive tasks (p < 0.05). In contrast, the migraine group showed imbalanced autonomic regulation, characterized by minimal changes in both sympathetic (LF band: 74.0–74.8 Hz) and parasympathetic activity (HF band: 25.9–25.1 Hz) (p > 0.05).Despite the similar cognitive test scores, migraine patients exhibited reduced variation in brain activity during cognitive tests and an imbalanced autonomic regulation, characterized by decreased sympathetic activity and increased parasympathetic activity.
Keywords: Migraine Disorders; Brain Mapping; Heart Rate; Autonomic Nervous System